A rose for Pinkerton - Kellogg, Steven (New York : Dial, 1981)
Pinkerton's family gets a cat named Rose so he can have a friend, and, when the dog starts acting like the cat and vice versa, they seek professional advice.
School Library Journal, March 2011
Booklist starred, April 2011
Horn Book, May 2011
2.6
K-3
K-3
Keywords: Dogs -- Fiction; Cats -- Fiction; Dogs -- Fiction; Cats -- Fiction